Critical Edition and Philological Analysis of the Isa 53 Text Based on the Coptic Manuscript of sa 52 (M 568) and Other Coptic Manuscripts of the Sahidic Dialect and the Greek Text of the Septuagint - Bąk, Tomasz Bartłomiej (Verbum Vitae, 2023)
The article is a critical edition, translation, and philological analysis of the Isa 53 text, prepared on the basis of the Coptic manuscript of sa 52 and other available manuscripts, written in the Sahidic dialect. Its first part outlines general information about the section of codex sa 52 (M 568) that contains the analyzed text. This is followed by a list and brief description of other manuscripts that contain at least some verses from sa 53. The most important part of the article is the presentation of the Sahidic text and its translation into English. The differences identified between the Coptic translation and the Greek Septuagint were presented in a table. It includes, for example, additions and omissions in the Sahidic translation, lexical changes, and semantic differences. The final part of the article aims to clarify more challenging philological issues observed either in the Coptic text itself or in its relation to the Greek text of the LXX.